Exercise Induced Asthma: An Overview - Cummiskey, J. (The American Journal of Medical Sciences, 2001)
Competitive sport in endurance events necessitates the use of full lung capacity. Regular training means that the lungs of athletes are exposed to large volumes of air. This exposure means that athletes inhale more cold, unhumidified and polluted air than the "normal" population. Because of these two reasons the incidence of bronchospasm in athletes is said to be higher than in the general population (18% compared to 3-10%). Exercise testing in athletes is the application of the engineering principle of testing under load. The rationale for exercise testing is aimed at provoking pathophysiological changes that are brought on by exercise, assessing the functional success of therapy and instilling confidence in the patient/athlete to participate in an exercise program. Exercise induced bronchospasm is only one manifestation of the asthmatic diathesis. It is not a distinct patho-physiological entity. Most patients in whom exercise is the predominant trigger of asthmatic symptoms will be found to have other triggers of asthmatic attacks by history or will have other triggers evolve over time. These triggers include hyperventilation, hypertonic saline and air pollutants.